Hatespeech and the Challenges of Post-Election Law Enforcement in Indonesia (Universitas PGRI Madiun, 2022)
Cases of hate speech in various post-election countries show the strengthening of community polarization that leads to horizontal conflicts that have the potential to threaten the disintegration of a country. This potential is even greater because of the public's distrust of law enforcement that has been carried out by the government so far. This paper is a type of normative research using a statute approach and a comparative approach. The results of the study show that the government must take prevention as early as possible and carry out law enforcement objectively so as to reduce the potential for social conflicts that lead to violence and state disintegration